Lung Cancer In Former Tuberculosis Patients at Arifin Achmad General Hospital, Riau Province - Martarita, Evitrie; Erdayani, Rita; Munir, Sri Melati; Fauzi, Zarfiardy Aksa; Simanjuntak, Arya Marganda (Respiratory Science, 2024)
Background: There is ongoing discussion over the connection between lung cancer and pulmonary tuberculosis (TB). Future lung cancer cases in Indonesia, which has the second-highest TB case burden, are a cause for concern. The purpose of this study is to ascertain the connection between TB and LC at Arifin Achmad General Hospital in the province of Riau. Method: From 2015 to 2018, we looked back on lung cancer patients at Arifin Achmad General Hospital in Riau Province who had received pulmonary tuberculosis and anti-tuberculosis treatment (ATT). Results: From 203 patients, 24 patients (11.8%) had histories of TB. The patients' ages were from 41 years to 60 years. The most prevalent pathological findings were adenocarcinoma in 13 patients (54.0%). The most common cancer stage was advanced stage IIIB in 7 patients (29.2%) Conclusion: The cases of TB infections were apparent in lung cancer patients, approximately around 11% of lung cancer cases. Therefore, it is necessary to assess the history of TB in lung cancer patients.